2001
DOI: 10.1007/bf02975165
|View full text |Cite
|
Sign up to set email alerts
|

Induction of oral tolerance to Japanese cedar pollen

Abstract: Oral tolerance is thought to play a role in preventing allergic responses and immune-mediated diseases. An improved mouse model of the oral tolerance to Japanese cedar pollen (JCP) as antigen was developed in order to detect induction of the tolerance, and the immunological characteristics of this model were also elucidated. Oral tolerance was induced by C3H/ HeN mice given an oral administration of 10 mg JCP 7 days before immunization with an i.p. injection of 0.1 mg JCP in complete Freunds adjuvant (CFA). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Many allergic rhinitis models mimic the major features of allergic rhinitis in humans (6,9,10,13,14). To study the relevant immunological mechanisms of Cj pollinosis and establish new therapeutic approaches, we had previously developed an allergic rhinitis model in B10.S mice elicited by histamine pretreatment and continuous intranasal antigen challenges for 5 days (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many allergic rhinitis models mimic the major features of allergic rhinitis in humans (6,9,10,13,14). To study the relevant immunological mechanisms of Cj pollinosis and establish new therapeutic approaches, we had previously developed an allergic rhinitis model in B10.S mice elicited by histamine pretreatment and continuous intranasal antigen challenges for 5 days (17).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple animal models of allergic rhinitis have been used to evaluate pharmacotherapy and immunotherapy (6,9,10,13,14). Nasal blockage and sneezing occur in guinea pigs given repeated inhalation challenges with Cj pollen (10).…”
mentioning
confidence: 99%
“…The majority of patients with allergic rhinitis are found to have high levels of allergen-specific IgE (Hashimoto et al, 1995). Many animal models for the study of allergic rhinitis have been reported (Nabe et al, 1998;Sato et al, 1999;Tamura et al, 1986;Kim et al, 2001;Murasugi et al, 2005). Murine models of allergic rhinitis are especially useful for investigating the immunological basis of this disease.…”
Section: Introductionmentioning
confidence: 98%
“…The majority of patients with allergic rhinitis are found to have high levels of allergen-specific IgE [4]. Many animal models for the study of allergic rhinitis have been reported [5,6,7]. Murine models of allergic rhinitis are especially useful for investigating the immunological basis of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Two major allergens, Cry j I and Cry j II, have been isolated from C. japonica pollen [8,9], and an effective animal model using Cry j I has been developed [5,6,7,10,11,12]. Antigen-induced nasal symptoms, late-phase nasal eosinophilia, and serum levels of antigen-specific IgE antibody were evaluated in an ovalbumin-sensitized BALB/c mouse model of allergic rhinitis [6,12,13].…”
Section: Introductionmentioning
confidence: 99%